DURABILITY OF ASPHALT CONCRETE MIXTURE (AC-WC) USING CRUMB RUBBER WASTE AS AN ADDITIONAL MATERIAL AND PALM FRUIT ASH AS FILLER - Benny Hamdi Rhoma Putra; Alfian Malik; Ermi Hidayati; Rizqy Ridho Prakasa; Elianora Elianora (Jurnal Pensil : Pendidikan Teknik Sipil, 2024)
The mixture of road pavement layers that is commonly used in Indonesia is a mixture of Asphalt Concrete (AC-WC). Addition of wastecrumb rubber (crumb rubber) in asphalt concrete mixture is a solution for highway planning and reducing waste pollutioncrumb rubber (crumb rubber) produced from a rubber tire factory. The purpose of this research is to determine the maximum percentage addition crumb rubber (crumb rubber) in the AC-WC mixture withfiller palm fruit bunch ash and to determine the residual strength index (RSI) value of the mixture which has a durability value that meets the requirements of General Specifications for Highways 2018 Revision 2. This study uses bitumen content with the percentage of mixed wastecrumb rubber used in the determination of OAC of 0%, 3%, and 6% by weight of asphalt andfiller palm fruit bunch ash 4% by weight of one AC-WC sample. The results of this study indicate testing marshall on variations crumb rubber 0% (without crumb rubber) as a normal mixture and 3% has met the specifications while the 6% variation does not. Maximum test results on the combination crumb rubber 3% resulted in the highest stability value of 1,028.85 kg at 0.5 hour immersion. The results of the durability test showed that the RSI value with a variation of 0% and 3% only fulfilled the 3 hour immersion time.